Análise exploratória de proteômica em tecido ruminal de bovinos Nelore (Bos indicus): impacto da alimentação e relação com a emissão de metano - Santos, Mykaelli Andrade (Universidade Federal de São Carlos, 2025)
Through proteomic approaches, this thesis explores the molecular adaptive mechanisms of the ruminal tissue in Nelore cattle (Bos indicus) in response to different nutritional interventions and variations in residual methane emissions. In the first chapter, the proteomic profiles of steers fed a conventional diet rich in corn grain were compared to those of steers receiving a diet formulated with agro-industrial by-products. The results demonstrated that the protein composition of the rumen is significantly modulated by the diet, reflecting specific cellular adaptations. The findings identified seven differentially abundant proteins related to structure, extracellular matrix remodeling, cytoskeletal organization, cellular regulation, and iron homeostasis. Notably, the reduced expression of FTH1 in the by-product diet suggests lower oxidative stress and inflammation. At the same time, the upregulation of six proteins indicates structural and metabolic adaptations within the ruminal tissue. In the second chapter, the thesis investigates the molecular mechanisms regulating methane emissions, a potent greenhouse gas, through a comparative analysis of the ruminal proteomic profile in cattle with differing residual methane emissions (RME) levels. Utilizing a shotgun proteomics approach, 37 differentially abundant proteins were identified between the high and low-emission groups. The data revealed that, in the low-emission group, proteins associated with protein degradation and energy metabolism were more abundant, suggesting more efficient fermentation and consequently reduced methane production. Conversely, the high-emission group exhibited upregulation of proteins involved in protein synthesis, lipid biosynthesis, and immune responses, which may indicate lower metabolic efficiency. Overall, the findings of this thesis provide new insights into the molecular mechanisms governing both the adaptive responses of ruminal tissue to varying nutritional profiles and methane production. These results may contribute to developing nutritional strategies to enhance feed efficiency and reduce greenhouse gas emissions in beef cattle production.
Exploratory proteomic analysis in ruminal tissue of Nellore cattle (Bos indicus): impact of feeding and relationship with methane emission
Keywords: Proteômica; Nelore; Rúmen; Metano; Proteomics; Methane; Rumen; CIENCIAS EXATAS E DA TERRA::QUIMICA